Young Australians' labour market engagement and job aspiration in the wake of the COVID‐19 pandemic. Issue 1 (5th September 2022) - Dinku, Yonatan; Yap, Mandy
Abstract: Young people tend to bear the brunt of adverse employment consequences of a crisis due mainly to the precarious nature of their job and their over‐representation among jobseekers who are having to find employment when jobs are scarce. Using quarterly welfare payment data for the period 2019–2021 from the Department of Social Services, we noted a marked increase in the percentage of 16‐ to 21‐year‐olds who received youth allowance (other) payments. While a greater proportion of Indigenous youth than non‐Indigenous youth received the payments from 2019 to 2021, the gap widened following the outbreak of the pandemic. Further, applying regression analysis to data from the 2019 and 2020 waves of the 2015 Cohort of the Longitudinal Study of Australian Youth (LSAY), we find no statistically significant change in individual‐level labour force status between 2019 and 2020. However, pandemic‐induced labour market crises appear to have been associated with reduced work hours, heightened career concerns and sustained nonemployment, where potential impacts are larger among traditionally vulnerable youth groups such as female, Indigenous and overseas‐born young persons. The study highlights the need for recognising the intersectionality of youth and other forms of identity (such as gender, Indigenous status and nativity) while designing labour market policies.